Cabozantinib in advanced non-clear-cell renal cell carcinoma: is it the way clearer now? - Pierro, Giulia Di; Mini, Enrico; Roviello, Giandomenico (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Martínez Chanzá et al. (1) investigated the activity of cabozantinib (an inhibitor of multiple tyrosine kinase receptors) in a multicentre, retrospective, cohort study carried out by 22 centres that involved 122 patients with metastatic renal cell carcinoma (RCC) with confirmed non clear cell histology treated in any line of therapy between 2015 and 2018.